Pasteurellosis in camels in Southern Mongolia: A case report - Erdenechimeg, Myagmar; Soyolmaa, Gurdorj; Cheng, Guofeng; Bayarsaikhan, Tsogtsaikhan; Dursahinhan, Altangerel Tsogtsaikhan; Lundaa, Tseveenjav; Munkhjargal, Tserendorj (Brazilian Journal of Veterinary Medicine, 2024)
Hemorrhagic septicemia (pasteurellosis) in animals, caused by Pasteurella multocida Trevisan 1887, is a significant but previously undocumented disease in Mongolian camels. Pasteurella multocida, a small Gram-negative coccobacillus, typically exists commensal in the nasopharynx of camels but can cause severe illness under certain environmental stressors. This study reports the first case of cameline hemorrhagic septicemia in Gobi region of Mongolia, specifically in Umnugobi province, where acute septicemia affected 26 camels, resulting in 10 deaths within 24-48 hours. Clinical signs included depression, inappetence, lethargy, increased rectal temperature, and paralysis of the lower lip. Surviving camels responded to treatment with Lactate Ringer solution and antibiotics. Postmortem examinations revealed acute pulmonary congestion and necrotic liver. Molecular diagnostic test, PCR, confirmed the presence of P. multocida with the identification of the KMT1 gene. This case underscores the potential for significant economic losses due to hemorrhagic septicemia in camels and highlights the need for early detection and treatment to mitigate its impact. The initial attempt at implementing a vaccination program effectively controlled the potential further outbreak. This study emphasizes the importance of continuous surveillance and preventive measures in managing hemorrhagic septicemia in livestock.